2022
DOI: 10.1155/2022/6730024
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Nursing Model Based on Rosenthal Effect on Self-Efficacy and Cognition of Life Meaning in Patients with Non-Small-Cell Lung Cancer

Abstract: Objective. To study the influence of nursing model based on Rosenthal effect on self-efficacy and cognition of life meaning in patients with non-small-cell lung cancer (NSCLC). Methods. 120 patients with NSCLC treated in the hospital were selected from November 2020 to November 2021 and were randomly divided into the nursing group and the Rosenthal group, with 60 cases in each group. The nursing group received routine nursing intervention, while the Rosenthal group was intervened by nursing model based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Whether the intervention can improve the emotional burden of the patients themselves deserves special attention. As shown in Table S1 , structured psychological intervention (including psychological support, health education for patients and their families, stress handling, coping skills, experience exchange, anticancer declaration learning), 22 , 34 , 41 , 42 , 44 relaxation training, 39 , 40 , 41 , 43 , 44 communication and exchange, 23 , 34 , 39 , 45 mindfulness therapy, 20 , 23 dignity enhancement and independence enhancement, 46 cognitive behavioral therapy (CBT), 21 and a nursing model intervention based on the Rosenthal effect 47 had been used to intervene the emotional burden of the patients. Structured psychological interventions, which integrated several components (such as health education, stress management, and coping skills), were beneficial in decrease of patients' emotional burden scores and could improve negative emotions (such as anxiety, depression, anger, confusion) in multiple ways.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Whether the intervention can improve the emotional burden of the patients themselves deserves special attention. As shown in Table S1 , structured psychological intervention (including psychological support, health education for patients and their families, stress handling, coping skills, experience exchange, anticancer declaration learning), 22 , 34 , 41 , 42 , 44 relaxation training, 39 , 40 , 41 , 43 , 44 communication and exchange, 23 , 34 , 39 , 45 mindfulness therapy, 20 , 23 dignity enhancement and independence enhancement, 46 cognitive behavioral therapy (CBT), 21 and a nursing model intervention based on the Rosenthal effect 47 had been used to intervene the emotional burden of the patients. Structured psychological interventions, which integrated several components (such as health education, stress management, and coping skills), were beneficial in decrease of patients' emotional burden scores and could improve negative emotions (such as anxiety, depression, anger, confusion) in multiple ways.…”
Section: Resultsmentioning
confidence: 99%
“… 46 The study by using the Rosenthal effect-based nursing model intervention also found that the patients had some reduction in SPB after the intervention. 47 However, one study illustrated that CBT had little effect on improving patients’ emotional burden. 21 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%